2015
DOI: 10.1016/j.ejphar.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib inhibits TGFβ-induced myofibroblast differentiation through Src-SRF Pathway

Abstract: Persistent myofibroblast differentiation is a hallmark of fibrotic diseases. Myofibroblasts are characterized by de novo expression of alpha smooth muscle actin (αSMA) and excess fibronectin assembly. Recent studies provide conflicting reports on the effects of tyrosine kinase inhibitor dasatinib on myofibroblast differentiation and fibrosis. Also, it is not fully understood whether dasatinib modulates myofibroblast differentiation by targeting Src kinase. Herein, we investigated the effect of dasatinib on cSr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Indeed, participation of Src in myofibroblast differentiation is further supported by a recent study that inhibition of Src can attenuate TGF-b1-induced myofibroblast differentiation in both National Institutes of Health (Bethesda, MD) 3T3 and fibrotic human lung fibroblasts in vitro. 34 Src activation is important in tissue fibrosis in mice with bleomycin-injured lung or UUO-damaged kidney 5,6 ; therefore, inhibition of MMT may contribute to the antifibrotic effects of Src-targted therapy. Thus, this is the first report to reveal and identify the causal relationship of Src and MMT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, participation of Src in myofibroblast differentiation is further supported by a recent study that inhibition of Src can attenuate TGF-b1-induced myofibroblast differentiation in both National Institutes of Health (Bethesda, MD) 3T3 and fibrotic human lung fibroblasts in vitro. 34 Src activation is important in tissue fibrosis in mice with bleomycin-injured lung or UUO-damaged kidney 5,6 ; therefore, inhibition of MMT may contribute to the antifibrotic effects of Src-targted therapy. Thus, this is the first report to reveal and identify the causal relationship of Src and MMT.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stretch‐induced Src activation in rats has been proven to augment intracellular signal transduction and the dissociation of junctional proteins from their cytoskeletal anchors, which may cause endothelial gap formation and an increase in vascular permeability . Previous studies of mouse embryonic fibroblasts and bleomycin‐induced murine lung fibrosis models indicated that selective Src kinase inhibition using PP2, a Src kinase inhibitor, reduced myofibroblast differentiation and pulmonary fibrosis . Blocking the Src pathway is likely to have some beneficial effects on the epithelial integrity, which may contribute to the reduced lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous murine study demonstrated that MV can augment bleomycin‐induced EMT through the Src pathway . The profibrotic effect of Src kinases could be an attractive target in the management of pulmonary fibrosis by using current novel tyrosine kinase inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the involvement of Src kinases in the non-canonical signaling of TGFβ contributing to fibroblast adhesion, migration, and myofibroblast-mediated ECM assembly suggesting that Src Kinases are pro-fibrotic [126-130]. Our laboratory has shown that selective Src kinase inhibition using PP2 mimicked the effect of dasatinib (Src-abl inhibitor) in blunting the αSMA expression and modest, but significant inhibition of fibronectin assembly via modulation of the expression of serum response factor (SRF) and hence in attenuating myofibroblast differentiation in both mouse and human fibroblasts [131]. …”
Section: Importance Of Src In Myofibroblast Differentiation Inflamentioning
confidence: 99%